Curricular internship at school for students in exercise and sports science first degree - Cereda, Ferdinando (Formazione & insegnamento, 2019)
Physical education is in the sciences of education and it is important in the definition and construction of educational and educational processes. The school and above all the primary school should play a central role in fostering the practice of a wide variety of motor experiences, providing not only tools and practice opportunities, but also knowledge and skills, which can guide the choice, motivate to participation and, not least, contribute to the well-being of pupils and teachers. Physical education consists of a set of coordinated activities, aimed at the physical and psycho-pedagogical development of the person. Gymnastics is in physical education as a set of movements regulated for various purposes, but can also be linked to the preparatory practice of a sporting discipline. The curricular internship represents an instrument of orientation of primary importance, as it offers the possibility of integrating the knowledge acquired during the university with the professional competences acquired in the workplace. It is therefore a very useful investment as a key to access the world of work.